USER INTERFACE WEBSITE E-DATABASE DI PT. XYZ - RAHMAN, ILHAM FATHUR; PUTRA, KURNIA RAMADHAN (e-Proceeding FTI, 2024)
Along with understanding the importance of interface design in various systems, it is also necessary to have a good design for the operation of digital interface systems. One of them is Material design which was developed by Google I/O in 2014. Material design carries the basic elements of real print design starting from typography design, grid, space, scale, color, and visual usage. PT. XYZ is a software company engaged in the Information Technology (IT) sector, e-Database was created to fulfill clients' needs so that they can search for government- related data easily and digitally. After carrying out and planning the e-Database user interface at PT. XYZ, it can be concluded as follows like the website user interface design has been successful using the Figma application. The appearance of the website has been successful using bootstrap so that it is even better and the interface for users and admins can be understood more easily. With the e-Database website application, it can make it easier for users to search for data related to governance. Abstrak Seiring dengan pemahaman akan pentingnya desain antarmuka dalam berbagai macam sistem, maka diperlukan pula adanya desain yang baik untuk pengoperasian sistem antarmuka digital. Salah satunya adalah Material design yang dikembangkan oleh Google I/O pada tahun 2014. Material design mengusung unsur-unsur dasar dari desain cetak yang nyata mulai dari desain tipografi, grid, ruang, skala, warna, dan penggunaan visual. PT. XYZ merupakan software company yang bergerak di bidang Teknologi Informasi (TI), e-Database dibuat untuk memenuhi client agar dapat mencari data terkait kepemerintahan dengan mudah dan digital. Setelah melaksanakan dan melakukan perencanaan user interface e-Database di PT. XYZ, maka dapat diambil kesimpulan sebagai berikut, perancangan user interface website telah berhasil menggunakan aplikasi Figma. Tampilan website telah berhasil menggunakan bootstrap sehingga menjadi lebih baik lagi dan interface untuk user dan admin dapat dipahami lebih mudah. Dengan adanya aplikasi website e-Database ini dapat mempermudah user untuk mencari data terkait kepemerintahan.